PEMETAAN POTENSI WISATA, PELUANG DAN TANTANGAN PENGEMBANGAN DESA WISATA PENGADANGAN BARAT, KABUPATEN LOMBOK TIMUR - Marham Jupri Hadi; Lume Lume; Meiyanti Widyaningrum (Journal of Tourism and Economic, 2022)
Pengadangan Barat Village has been designated as a tourist village in 2021, however it has not shown its existence as an attractive rural tourist destination to visit upto the present. This is due to the absence of a master plan for the development of tourism. This study aimed to map the tourism potential of Pengadangan Barat Village as well as the opportunities and challenges of its development into a village-based tourist destination. Using qualitative research method, this research involved the village government, members of tourism awareness groups, and village communities to become informants. Data were collected through participant observation techniques, FGDs, interviews and documentation and were analyzed qualitatively. This research revealed three categories of tourism potential owned by the Pengadangan Barat tourism village, namely natural potential, cultural and historical potential, and human resource potential. This research also concluded that western tourism villages can be developed into destinations for educational tourism, agritourism and sports or adventure tourism. The challenges of developing this village were  in the form of the capacity of members of tourism awareness groups, village government policies, community participation and competition with other tourism villages. These challenges could be addressed by conducting intensive communication and cooperation with various relevant parties and asking for assistance from practitioners and academics.